2022
DOI: 10.1083/jcb.202106046
|View full text |Cite
|
Sign up to set email alerts
|

ER-lysosome lipid transfer protein VPS13C/PARK23 prevents aberrant mtDNA-dependent STING signaling

Abstract: Mutations in VPS13C cause early-onset, autosomal recessive Parkinson’s disease (PD). We have established that VPS13C encodes a lipid transfer protein localized to contact sites between the ER and late endosomes/lysosomes. In the current study, we demonstrate that depleting VPS13C in HeLa cells causes an accumulation of lysosomes with an altered lipid profile, including an accumulation of di-22:6-BMP, a biomarker of the PD-associated leucine-rich repeat kinase 2 (LRRK2) G2019S mutation. In addition, the DNA-sen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 82 publications
4
52
0
Order By: Relevance
“…The ER is relatively enriched in those lipid species compared to endo-lysosomes (Escribá et al, 2015; Guo et al, 2009; Horvath and Daum, 2013; Pogozheva et al, 2022; Reglinski et al, 2020; Tauchi-Sato et al, 2002; van Meer and de Kroon, 2011; van Meer et al, 2008). Despite this, the levels of phosphatidylcholine, phosphatidylserine, phosphatidylinositol, and sphingomyelin increase in the lysosome in VPS13C knockout clones (Hancock-Cerutti et al, 2022). Intriguingly, this suggests that VPS13C-mediated lipid transfer can be compensated for by other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ER is relatively enriched in those lipid species compared to endo-lysosomes (Escribá et al, 2015; Guo et al, 2009; Horvath and Daum, 2013; Pogozheva et al, 2022; Reglinski et al, 2020; Tauchi-Sato et al, 2002; van Meer and de Kroon, 2011; van Meer et al, 2008). Despite this, the levels of phosphatidylcholine, phosphatidylserine, phosphatidylinositol, and sphingomyelin increase in the lysosome in VPS13C knockout clones (Hancock-Cerutti et al, 2022). Intriguingly, this suggests that VPS13C-mediated lipid transfer can be compensated for by other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…VPS13C also localises at ER-lipid droplet, at ER-endo-lysosome jucntions (Kumar et al, 2018). Here, it is thought to interact with the GTPase Rab7 (McCray et al, 2010, Hancock-Cerutti et al 2022). Tethered at Golgi-endosome contact sites are VPS13B proteins (Seifert et al, 2011), which were shown to bind Rab6 (Seifert et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Using a CRISPR-iPSC-based approach, a group generated VPS13C knockout iPSC-derived neuronal cell lines in which they studied knockout-mediated lysosomal function alteration. Combining these insights with that derived from VPS13C knockout HeLa cells and VPS13C −/− mice, the group demonstrated the perturbation of lysosomal lipid homeostasis in VPS13C -deficient cells, thereby suggesting the involvement of VPS13C in PD pathogenesis-relevant pathways (Hancock-Cerutti et al 2022 ).…”
Section: Parkinson’s Diseasementioning
confidence: 96%
“…Defective mitochondrial membrane structure and increased permeability are key causes of mtDNA leakage. Altered lipid composition in the mitochondrial membrane leads to increased mitochondrial permeability and mtDNA leakage [ 31 ]. Mitochondrial damage caused by multiple factors is often accompanied by mtDNA leakage.…”
Section: Common Types Of Mtdna Damagementioning
confidence: 99%